THE MALE FEMINISM OF KRISHNA IN CHITRA LEKHA BANERJEE DIVAKARUNI’S THE PALACE OF ILLUSIONS - Nikodemus Yudho Sulistyo (Jurnal Ilmiah Spectral, 2021)
Men can also be a feminist. They can respond to the oppression and discrimination toward women and struggle to change the situation to promote gender equality. This movement is called male feminism which can be also depicted in a literary work. This research seeks to find male feminism of Krishna in the novel The Palace of Illusion written by Chitra Lekha Banerjee using feminist approach while the method used in this research is library research. Krishna is a very famous character in Indian epic story of Mahabharata and holy figure in Hinduism. The result shows that Krishna is found as a male feminist who supports the equality among men and women through the main character of Panchaali as reflected by his actions and thoughts.